Robot‐Assisted Laparoscopic Radical Nephrectomy in a Renal Cell Carcinoma Patient With Severe Scoliosis: A Case Report - Tatsuya Kawamura; Daiki Ikarashi; Ayato Ito; Ei Shiomi; Shigekatsu Maekawa; Renpei Kato; Mitsugu Kanehira; Ryo Takata; Wataru Obara (IJU Case Reports)
ABSTRACT Introduction Laparoscopic nephrectomy in patients with severe scoliosis presents significant challenges due to altered anatomy and limited space. This case report discusses using robot‐assisted laparoscopic radical nephrectomy in such a scenario. Case Presentation A 68‐year‐old man with severe right convex scoliosis was diagnosed with cT3aN0M0 right locally advanced renal cell carcinoma. Given the anatomical distortions caused by scoliosis, traditional laparoscopic techniques posed difficulties. We opted for robot‐assisted laparoscopic radical nephrectomy, carefully planning the port placement and surgical approach to accommodate the patient's unique anatomical features. Conclusion This is the first reported instance of robot‐assisted laparoscopic radical nephrectomy in a patient with severe scoliosis. The successful outcome demonstrates the feasibility and benefits of robotic assistance in overcoming the technical difficulties associated with scoliosis, offering a viable surgical option for similar cases.